Hornets Have It: A Conserved Olfactory Subsystem for Social Recognition in Hymenoptera? - Antoine Couto; Aniruddha Mitra; Denis Thiéry; Frédéric Marion-Poll; Jean-Christophe Sandoz (Frontiers Media S.A., 2017)
Eusocial Hymenoptera colonies are characterized by the presence of altruistic individuals, which rear their siblings instead of their own offspring. In the course of evolution, such sterile castes are thought to have emerged through the process of kin selection, altruistic traits being transmitted to following generation if they benefit relatives. By allowing kinship recognition, the detection of cuticular hydrocarbons (CHCs) might be instrumental for kin selection. In carpenter ants, a female-specific olfactory subsystem processes CHC information through antennal detection by basiconic sensilla. It is still unclear if other families of eusocial Hymenoptera use the same subsystem for sensing CHCs. Here, we examined the existence of such a subsystem in Vespidae (using the hornet Vespa velutina), a family in which eusociality emerged independently of ants. The antennae of both males and female hornets contain large basiconic sensilla. Sensory neurons from the large basiconic sensilla exclusively project to a conspicuous cluster of small glomeruli in the antennal lobe, with anatomical and immunoreactive features that are strikingly similar to those of the ant CHC-sensitive subsystem. Extracellular electrophysiological recordings further show that sensory neurons within hornet basiconic sensilla preferentially respond to CHCs. Although this subsystem is not female-specific in hornets, the observed similarities with the olfactory system of ants are striking. They suggest that the basiconic sensilla subsystem could be an ancestral trait, which may have played a key role in the advent of eusociality in these hymenopteran families by allowing kin recognition and the production of altruistic behaviors toward relatives.